A synopsis of the Panamanian species of Ilex (Aquifoliaceae) / W. J. Hahn - Hahn, Wiliam James (2007)
The species of Ilex (Aquifoliaceae) native to Panama are treated in a synoptic fashion. Three new species are described: Ilex fortunensis, Ilex maxima, and Ilex stellata
il byn
Keywords: Aquifoliaceae; Ilex